2018
DOI: 10.3847/1538-4357/aacc6c
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Photospheric Features in the Near-infrared Spectrum of a Class 0 Protostar

Abstract: We present a near-infrared K-band R 1500 Keck spectrum of S68N, a Class 0 protostar in the Serpens molecular cloud. The spectrum shows a very red continuum, CO absorption bands, weak or non-existent atomic metal absorptions, and H 2 emission lines. The near-IR H 2 emission is consistent with excitation in shocks or by X-rays but not by UV radiation. We model the absorption component as a stellar photosphere plus circumstellar continuum emission with wavelength-dependent extinction. A Markov Chain Monte Carlo a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 38 publications
2
23
1
Order By: Relevance
“…By assuming a typical reddening as A V = 20 mag and R V = 3.1, these flux ratios will be increased by 17% after de-reddening. This result rules out the possibility of pure UV excitation, similar to a recent measurement of a Class 0 protostar (S68N; Greene et al 2018). This method is also applied to other three objects (v20, v473 and v699) which have detectable H 2 2 -1 S(1) lines.…”
Section: V815: Launching Of Outflow On a Short Timescalesupporting
confidence: 80%
“…By assuming a typical reddening as A V = 20 mag and R V = 3.1, these flux ratios will be increased by 17% after de-reddening. This result rules out the possibility of pure UV excitation, similar to a recent measurement of a Class 0 protostar (S68N; Greene et al 2018). This method is also applied to other three objects (v20, v473 and v699) which have detectable H 2 2 -1 S(1) lines.…”
Section: V815: Launching Of Outflow On a Short Timescalesupporting
confidence: 80%
“…There have been few other Class 0s that have had their near-IR spectroscopic observations analyzed for both emission and absorption components. Serpens S68N also exhibited H 2 emission but was absent in Br γ and showed CO bands in absorption rather than emission (Greene et al 2018). We report the incidence rates of these features in emission among our 5 continuumdetected Class 0s (Figure 1) and Serpens S68N in Table 5.…”
Section: 2mentioning
confidence: 79%
“…At a disk accretion rate of ∼10 −6 M yr −1 , a protostar can sustain a stellar magnetosphere (and produce the Br γ line profiles we observe) if it has developed a strong, organized stellar magnetic field. If our Class 0 sources have a protostellar mass of 0.2 M (as measured for the similarly low-luminosity Class 0 source L1527 IRS; Tobin et al 2012) and a stellar surface gravity (log g) of 2.38 (as measured for Serpens S68N; Greene et al 2018), protostellar radii are ∼4-5 R . If the Class 0 sources further have a disk accretion of ∼10 −6 M yr −1 and their stellar magnetospheres truncate the inner disk at ∼2 stellar radii (as measured for the Class I YLW 15; Greene & Lada 2002), the required protostellar magnetic field strength is ∼1 kG (Hartmann et al 2016 and references therein).…”
Section: 2mentioning
confidence: 81%
See 1 more Smart Citation
“…A list of research groups working on this issue can be found in Dumusque et al (2017) and in Nelson et al (2020). MCMC are also used in spectroscopic studies (Greene et al 2018;Casasayas-Barris et al 2020).…”
Section: Introductionmentioning
confidence: 99%